The interactive effects of recovery mode and duration on subsequent repeated sprint performance - Brown, J.; Glaister, M. (The Journal of Strength and Conditioning Research, 2014)
The aim of this study was to examine the interactive effects of recovery mode and duration on subsequent repeated short sprint (RSS) performance. Ten male recreational athletes (age, 27.9 ± 5.0 years; height, 1.80 ± 0.07 m; mass, 81.6 ± 13.5 kg) performed 4 randomized trials consisting of a 30-second cycle sprint, followed by a specified recovery period (45 or 180 seconds), and a subsequent set of RSS (7 × 5 seconds, 20-second passive rest periods). Recovery mode was either active (AR; 70% of the power output at lactate threshold) or passive (PR). Mean heart rate and VO2 were significantly higher (p kleiner/gleich 0.05) in AR than in PR over both recovery durations. Although the difference in VO2 reached significance after 10-15 seconds, a significant (p kleiner/gleich 0.05) difference in heart rate was observed only after 26 seconds (45-second trials) - 75 seconds (180-second trials). Blood lactate was significantly (p kleiner/gleich 0.05) lower in AR than in PR only after 135 seconds (mean difference, 2.16 mmol/L; 95% likely range, 0.77-3.55 mmol/L). Mean peak power output in the RSS test was significantly (p kleiner/gleich 0.05) higher following PR45 than AR45 (12.0 ± 1.4 vs. 11.4 ± 1.4 W/kg) and following AR180 than PR180 (12.7 ± 1.2 vs. 12.0 ± 1.2 W/kg). In conclusion, when rest periods are short, a PR strategy appears to optimize subsequent RSS performance. However, as the recovery duration increases subsequent RSS performance appears to benefit from an AR strategy.